Multi-mode ultra-strong coupling in circuit quantum electrodynamics. (December 2017) - Bosman, Sal; Gely, Mario; Singh, Vibhor; Bruno, Alessandro; Bothner, Daniel; Steele, Gary
Abstract With the introduction of superconducting circuits into the field of quantum optics, many experimental demonstrations of the quantum physics of an artificial atom coupled to a single-mode light field have been realized. Engineering such quantum systems offers the opportunity to explore extreme regimes of light-matter interaction that are inaccessible with natural systems. For instance the coupling strengthg can be increased until it is comparable with the atomic or mode frequencyω a, m and the atom can be coupled to multiple modes which has always challenged our understanding of light-matter interaction. Here, we experimentally realize a transmon qubit in the ultra-strong coupling regime, reaching coupling ratios ofg /ω m = 0.19 and we measure multi-mode interactions through a hybridization of the qubit up to the fifth mode of the resonator. This is enabled by a qubit with 88% of its capacitance formed by a vacuum-gap capacitance with the center conductor of a coplanar waveguide resonator. In addition to potential applications in quantum information technologies due to its small size, this architecture offers the potential to further explore the regime of multi-mode ultra-strong coupling. Quantum mechanics: Light-matter interaction in the extreme When light couples to an atom, the two exchange quanta of energy at a frequency called the coupling rate. It has been predicted that by increasing this coupling to rates much larger than anything present in nature, "spooky" entangled states of light would appear. A team led by Gary Steele in the Netherlands at the Delft University of Technology has realized extreme coupling rates using man-made superconducting atoms coupled to microwave "light" in electromagnetic resonators. In the experiment, the atom is very strongly coupled to many different modes of the resonator at the same time, a problem which led to long-standing puzzles in quantum mechanics. Studying such engineered quantum atoms may help us better understand the fundamental interaction of light and matter.